Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145299
|View full text |Cite
|
Sign up to set email alerts
|

Integrating local and remote worlds through channel blending

Abstract: Recent advances in ubiquitous technology have greatly changed the way people stay connected. We conducted an in-depth video shadowing study to observe how close-knit groups use all the technology at their disposal to stay in touch and share their lives. We observed a pattern of related behaviors that we call channel blending, the integration of interactions and content over multiple channels into one coherent conversation, often including both local and remote participants. Channel blending is the opposite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Related to channel switching is the practice of channel blending. Isaacs and colleagues recently studied how channel blending, or the act of using multiple modes of communication at the same time, allows individuals to coordinate and share experiences [14]. While Isaacs et al's work did not focus on channel switching per se, the current work builds on their suggestion to "think about coherent social acts that may take place over time and across channels" (p. 626) rather than focus on acts of FtF and mediated communication in isolation.…”
Section: Channel Switchingmentioning
confidence: 99%
“…Related to channel switching is the practice of channel blending. Isaacs and colleagues recently studied how channel blending, or the act of using multiple modes of communication at the same time, allows individuals to coordinate and share experiences [14]. While Isaacs et al's work did not focus on channel switching per se, the current work builds on their suggestion to "think about coherent social acts that may take place over time and across channels" (p. 626) rather than focus on acts of FtF and mediated communication in isolation.…”
Section: Channel Switchingmentioning
confidence: 99%
“…We see opportunities for innovation where elements of social support, validation, mentoring, and private interactions are combined with YouTube affordances (lively video demonstrations, approachability, repeatability, and access to expertise world-wide). Here Isaacs et al [20]'s channel blending study should also be consulted. 4.…”
Section: Design Private Communication Channels In Peerproduction Sitesmentioning
confidence: 99%
“…The solutions should not increase the burden of local governments, but to rethink activities that planning departments already engage in. Many departments use crowdsourcing mechanisms to stimulate citizen feedback and employ social media based outreach [3,7,14,27,31]. The proposed solutions intend to lower technology barriers for citizens and planners by encouraging more natural online interactions.…”
Section: Implications and Recommendations For Designmentioning
confidence: 99%
“…We recommend facilitation of deliberation through guided tools. Isaacs et al [14] observed that when small groups attempt to carry on synchronous interaction with local and remote participants, it generally involved one person playing the role of a "pivot person," integrating the contributions of local and remote participants. Since current newspaper forums do not support this configuration, facilitation requires targeted skill-training to avoid breakdowns in the natural conversation flow that occurs in current forums.…”
Section: Opportunity To Advance: Encourage Reason Giving To Accompanymentioning
confidence: 99%
See 1 more Smart Citation